2016
DOI: 10.1016/j.jceh.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Presentation of Leishmaniasis

Abstract: Leishmaniasis or kala-azar is a protozoan disease that can present as cutaneous, mucocutaneous, visceral, and disseminated disease. In India, it is usually localized in distinct areas of Bihar, Jharkhand, West Bengal, and parts of Eastern Uttar Pradesh. Visceral leishmaniasis (VL) involves the visceral organs, mainly the liver, the spleen and bone marrow. VL is characterized by prolonged fever, massive splenomegaly, weight loss, progressive anemia, pancytopenia, and hypergammaglobulinemia, and can be complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Furthermore, different case reports supported the present study and reported liver dysfunction with the raised value of serum AST, ALT, and bilirubin from VL patients. [14][15][16][17][18][19] Similarly, studies conducted in India and Bangladesh also reported abnormally high liver inflammatory enzymes like ALT, AST, and ALP in VL patients. 6,20 This may be attributed to the levels of particular circulating cytokines during the inflammatory processes observed in active VL disease could be a determinant and consequence of severe liver disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, different case reports supported the present study and reported liver dysfunction with the raised value of serum AST, ALT, and bilirubin from VL patients. [14][15][16][17][18][19] Similarly, studies conducted in India and Bangladesh also reported abnormally high liver inflammatory enzymes like ALT, AST, and ALP in VL patients. 6,20 This may be attributed to the levels of particular circulating cytokines during the inflammatory processes observed in active VL disease could be a determinant and consequence of severe liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Besides different case reports conducted in India, Turkey, and a cohort study conducted in Brazil showed that elevated total and direct bilirubin in VL patients. 18 , 19 , 23 This may attribute to hemolysis of red blood cells and sequestration and destruction of red blood cells (RBC) in enlarged spleen of VL patients. 24 However, this study was not in agreement with the study conducted in Iraq and which were reported no significant difference in the mean value of serum bilirubin between VL patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 35 Severe anemia, malnutrition and long duration of illness were shown to be associated with an increased risk of death. 25 , 36 These issues should be addressed in evaluating and managing patients with VL. The marked bone marrow eosinopenia associated with marked peripheral blood eosinopenia are the characteristics which were most common in our patients with VL and usually are not reported both together in other simulating illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…In 27 cases, enhanced uptake was seen in the bone marrow. Of these, five cases were IS patients, 9,20,21,24,25 20 cases were in immunocompetent patients, 7,14,15,18,22,23,26,29 and in two cases, the immune state was unknown. 19,27 Bone marrow biopsy revealed Leishmania spp.…”
Section: Resultsmentioning
confidence: 99%
“…in three non-IS patients. 14,15,18 Of the remaining cases with enhanced bone marrow uptake, three biopsies were negative 22,23,29 and 14 cases did not undergo bone marrow biopsy or had no information available. 7,26 Lymph node involvement was only mentioned in 13 cases (five IS [8][9][10]21,24 and eight non-IS 7,16,28 ).…”
Section: Resultsmentioning
confidence: 99%